Analisis Hukum Analisis Hukum Acara Pidana Terhadap Tanggung Jawab Penyidik Kepolisian Dalam Pengelolaan Barang Bukti (Studi kasus di POLRESTA Kupang Kota) - Tirthon Djami Riwu; Renny R Masu; A Resopijani (Law Faculty, Nusa Cendana University, 2026)
The management of evidence is a crucial aspect within the criminal procedural law system, ensuring the legality and continuity of judicial processes. This study examines the implementation of evidence management at the Kupang City Police Resort (Polresta Kupang Kota) in accordance with the Indonesian Criminal Procedure Code (KUHAP) and relevant regulations, while analyzing the responsibilities of investigators in handling such evidence. Employing a juridical empirical methodology, the research integrates normative legal analysis with empirical data collection through interviews and document review. Findings indicate that evidence management at Polresta Kupang Kota encounters significant challenges, including limited storage facilities, inadequate maintenance budgets, and predominantly manual administrative processes. The absence of a dedicated Standard Operating Procedure (SOP) for evidence management leads to inconsistent practices, potentially undermining the accountability and integrity of the evidence. Moreover, delays in administrative approvals, particularly for the destruction of perishable evidence, pose risks to evidentiary value and public safety.Consequently, the study recommends developing comprehensive SOPs, implementing digital record-keeping systems, and strengthening internal and external oversight mechanisms. These measures aim to enhance the efficiency, transparency, and legal compliance of evidence management processes, thereby safeguarding the rights of involved parties and upholding the rule of law within the criminal justice system.